2017
DOI: 10.1590/0037-8682-0209-2017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of carbapenem-resistant Enterobacteriaceae in a tertiary-level reference hospital in Rio Grande do Sul, Brazil

Abstract: Introduction:The rapid global spread of carbapenem-resistant Enterobacteriaceae (CRE) is a threat to the health system. Methods: We evaluated the antimicrobial susceptibility profiles of 70 CRE isolated in a tertiary hospital in Brazil between August and December 2015, and determined their resistance mechanisms. Results: The most prevalent microorganism was Klebsiella pneumoniae (95.7%); it showed high-level resistance to carbapenems (>98%), with sensitivity to colistin (91.4%) and amikacin (98.6%). The bla KP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 11 publications
3
9
0
1
Order By: Relevance
“…Another study by Arnold et al,16 concluded that Klebsiella pneumonia Carbapenemase (KPC) producing bacteria have created challenges for clinicians due to highly drug resistance, resulting in delays in effective treatment so the effective antibiotics are limited to Polymyxin, Tigecyclines and occasionally aminoglycosides, which is similarto our study that shows predominance of KPC from Enterobacteriaceae showing 100% sensitivity towards Polymyxin B and Tigecycline.Similarly, Amikacin, Piperacillin/Tazobactam and Tobramycin could be used as good alternatives as almost half of Carbapenem resistant Enterobacteriaceae were found sensitive to them. This study is similar to the study done by Almugadam et al14 and Lorenzoni et al15 which shows 83.3% (10/12) and increased rate 98.6% respectively, rate of sensitivity of Amikacin in Carbapenem resistant enterobacteriaceae.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Another study by Arnold et al,16 concluded that Klebsiella pneumonia Carbapenemase (KPC) producing bacteria have created challenges for clinicians due to highly drug resistance, resulting in delays in effective treatment so the effective antibiotics are limited to Polymyxin, Tigecyclines and occasionally aminoglycosides, which is similarto our study that shows predominance of KPC from Enterobacteriaceae showing 100% sensitivity towards Polymyxin B and Tigecycline.Similarly, Amikacin, Piperacillin/Tazobactam and Tobramycin could be used as good alternatives as almost half of Carbapenem resistant Enterobacteriaceae were found sensitive to them. This study is similar to the study done by Almugadam et al14 and Lorenzoni et al15 which shows 83.3% (10/12) and increased rate 98.6% respectively, rate of sensitivity of Amikacin in Carbapenem resistant enterobacteriaceae.…”
supporting
confidence: 92%
“…towards Nitrofurantoin among Carbapenem resistant Enterobacteriaceae.When Carbapenem resistant samples were subjected to other antibiotic sensitivity test, all strains of Carbapenem resistant Enterobacteriaceae were found to be sensitive to Colistin, Polymyxin B and Tigecycline. Similar type of study was conducted by Lorenzoni et al,15 which show high level of sensitivity to Colistin (91.4%) among Klebsiella pneumoniae. Another study by Arnold et al,16 concluded that Klebsiella pneumonia Carbapenemase (KPC) producing bacteria have created challenges for clinicians due to highly drug resistance, resulting in delays in effective treatment so the effective antibiotics are limited to Polymyxin, Tigecyclines and occasionally aminoglycosides, which is similarto our study that shows predominance of KPC from Enterobacteriaceae showing 100% sensitivity towards Polymyxin B and Tigecycline.Similarly, Amikacin, Piperacillin/Tazobactam and Tobramycin could be used as good alternatives as almost half of Carbapenem resistant Enterobacteriaceae were found sensitive to them.…”
supporting
confidence: 70%
“…Data regarding important CRE studies in Taiwan and other countries are shown in Table 1 . There were big variations in the rates of CPE among clinical CRE isolates in Taiwan as compared to those from other countries ( Lorenzoni et al, 2017 ; Woodford et al, 2017 ; Laolerd et al, 2018 ). It is notable that persistently high KPC-2 rates (73.9% in 2012, and 61.1% in 2015) and emergence of KPC-17 as well as KPC-34 since 2014 were observed ( Chiu et al, 2018 ).…”
Section: Prevalence and Mortality Rates Of Carbapenemase-producing Enmentioning
confidence: 88%
“…Among Enterobacteriaceae species carbapenem resistance is a big problem especially in K. pneumoniae. A study performed on 70 CRE isolates at a tertiary hospital in Brazil in 2015 showed that the most prevalent microorganism was K. pneumoniae (95.7%) with a high-level resistance to carbapenems (> 98%) [16]. In a study from Turkey evaluating 181 CRE isolates, about half of the isolates displayed multidrugresistance [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, in isolates with ESBLs or cell wall permeability defects, it can cause increased level of cephalosporin and carbapenem resistance. Furthermore, co-expression of OXA-48 and ESBLs (CTX-M-15, SHV) and coexpression of OXA-48 and AmpC enzymes in CRE were reported [11,16,17]. In the presented study, out of the 57 CRKP isolates, the frequency of carbapenemases determined were blaOXA-48 (82.45%), blaOXA-55 (40.35%), blaOXA-51 (3.50%), blaOXA-23 (1.75%), blaOXA-24 (1.75%), blaIMP (1.75%).…”
Section: Discussionmentioning
confidence: 99%